Carrier recombination in polymer fullerene solar cells probed by reversible exchange of charge between the active layer and electrodes induced by a linearly varying voltage - Hofstad, Tom G. J. van der; Di Nuzzo, Daniele; Reenen, Stephan van; Janssen, René A. J.; Kemerink, Martijn; Meskers, Stefan C. J. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2013)
The use of a voltage pulse that varies linearly with time and that is symmetric in time around t = 0 allows for simultaneous determination of (photo)capacitance and (photo)conductance of polymer solar cells. From the measured capacitance, an average density of reversibly extractable carriers is determined, and the result is compared to numerical drift-diffusion simulations. Results are in agreement with large charge densities near the contacts that can be exchanged with the electrode in a thermodynamically reversible manner upon changing the voltage. The combined determination of capacitance and conductance yields a relaxation time τrel for photogenerated charge carriers. Results on thermally annealed poly(3-hexylthiopene):fullerene bulk heterojunction solar cells indicate τrel ∼ 2 μs, limited by extraction and not significantly affected by bimolecular recombination under intensities up to 1 sun. In contrast, for small bandgap poly(diketopyrrolopyrrole-alt-quinquethiophene)-fullerene solar cells with ∼5% power conversion efficiency, τrel is limited by bimolecular recombination. This illustrates the need for very fast charge transport rates to avoid losses due to bimolecular recombination in solar cells with high charge generation rates. Conclusions from the charge exchange experiments are confirmed by time domain measurements using pulsed illumination.